Hemodynamic Pro?le of Laryngeal Mask Airway Insertion Compared to Laryngoscopy and Tracheal Intubation - Prasad, Ram Nandan (Academia Anesthesiologica International, 2020)
Background: Endotracheal intubation by laryngoscopy is one of the most famous and frequent methods for securing the airway. This study compares the modifications in hemodynamic parameters in hypertensive patients following laryngoscopic endotracheal intubation or laryngeal mask airway insertion. Subjects and Methods : Fifty patients between the ages of 35-70 years of either gender with a history of Hypertension of ASA grade II planned for elective surgery were selected. They were separated into 2 groups: group LMA and group ET. LMA insertion or tracheal intubation was executed following the induction of anesthesia with Propofol and succinylcholine. The heart rate, mean arterial pressure and rate pressure product were calculated after induction and instantly following insertion /intubation and then after 1, 3, 5 minutes. Results: The heart rate was augmented after induction and continued to be high for more than 3 minutes after LMA insertion and tracheal intubation. The increase in Heart rate was more in the ET group than the LMA group. The values remained high for 5 minutes in Group ET and only for 3 minutes in Group LMA. Group LMA had lower values at all times when compared to Group ET. Conclusion: Our study concludes that the insertion of the laryngeal mask airway grounds a lesser hemodynamic reaction than tracheal intubation in hypertensive patients.